Security mechanism for maritime territory and frontier surveillance in naval operations using wireless sensor networks. (3rd April 2021) - Jain, Usha; Hussain, Muzzammil
Summary: In an underwater environment, wireless sensor networks (WSNs) have more potential applications such as homeland safety, naval surveillance, and pollution & exploration monitoring. Underwater wireless sensor networks (UWSNs) help in decreasing the rate of causalities and provide efficient ways for monitoring the underwater activities of the other countries. UWSNs can be efficiently used by the navy to monitor suspicious activities and also to counter‐attack any terrorist or enemy attacks. As usual, deploying wireless sensor networks underwater is not only challenging due to environment and constrained resources but also is vulnerable to security attacks. Thus, security is an unexplored and crucial aspect of UWSNs. Here, we define a node authentication mechanism for UWSNs for securing frontier lines, maritime territory, and naval surveillance. The proposed authentication protocol is based on symmetric‐key cryptography and secures against impersonation, masquerade, Sybil, and many more other attacks. We have analyzed the proposed protocol both formally and automatedly and were unable to find any possible security attack on the proposed protocol. The experimental analysis of the mechanism proved that the proposed mechanism consumes less energy compared to the existing mechanisms. Hence, the proposed mechanism can be easily adopted for maintaining the security of maritime territory and reduce the causalities in naval operations.